PTH-129 Significant cost savings utilising a regional prescribing approach to mesalazine therapy in inflammatory bowel disease. (June 2019) - Tham, Jennifer; Sharp, Tracey; Ryan, Paul; Pentney, Ross; Watts, David; Morris, John
Abstract : Introduction: The West of Scotland (WoS) Gastroenterology Prescribing Subgroup is a clinically led multi-disciplinary group supporting the effective prescribing of GI medicines in the five health boards (HB) in the WoS with a population of 2.78 million. Group membership includes gastroenterologists, pharmacists, IBD nurses, with Regional Planning and National Services Scotland representation. The group builds regional consensus on an agent of choice in defined clinical indications where there are a number of therapeutic options. In Inflammatory bowel disease (IBD) the British National Formulary states there is no difference in efficacy between different oral mesalazine brands (5-ASA). Methods: We identified the opportunity to negotiate a preferential price of 5-ASA and to recommend this as the 1st line agent in patients initiating 5-ASA therapy. National Procurement Scotland, undertook a price review of the different mesalazine brands on behalf of the WoS Group. For products included in consideration, the recommended 1st line agent was the product with the lowest medicine cost to NHS Scotland in primary care, based on maintenance doses agreed by the WoS Gastro Group. In addition we recommended a switch from Asacol to Octasa in patients on maintenance 5-ASA therapy. Post guidance prescribing data was obtained from Information Services Directorate, Scotland. Results: WoS guidance recommended Salofalk preparations at 3 g/1.5 g for induction and maintenance of remission for new patients with IBD. From May 2017 the guidance was disseminated to secondary and primary care via clinical advisory channels, therapeutics committee and pharmacists. In the first year, uptake of the new guidance across the five HB was median 40% (range 17 -50%) patients initiated on Salofalk compared to other mesalazine brands. From May 2017 to September 2018 there has been a total cost avoidance of £109, 618 through initiating new patients on Salofalk increasing sequentially. These savings are highlighted in figure 1. With respect to cost savings with switching Asacal to Octasa, two HBs were excluded as they had already implemented a switch since 2016. In the three remaining HBs, switches were achieved in 71, 81 and 92% of patients respectively, incurring a saving of £143, 633. Conclusions: Our data shows a regional approach to cost effective prescribing of 5 ASA in IBD has been successful both in terms of implementation of the guidance and resulted in cost savings to NHS WoS of over £0.25 M.